Megathrusts, Megavalving and Mineralisation – Perturbation of Hydrothermal and Magmatic Flow Systems by Subduction Thrust Ruptures - R H. Sibson (The Australasian Institute of Mining and Metallurgy, 2011)
Magmatic and/or hydrothermal fluid systems in island or mountain arcs self-organise to critical states subject to perturbation by changes in the regional stress, which plays a controlling role in the containment of overpressured fluids. Whether the magmatic arc is under compression (eg Andes, northern Honshu) or extension (eg Taupo Volcanic Zone, New Zealand) is a key factor controlling the ease of magmatic or hydrothermal fluid ascent. Abrupt changes in the stress regime have the potential to induce major episodes of fluid redistribution. Large earthquake ruptures along plate boundaries may induce such changes over broad areas, also contributing to fluid redistribution by renewing fault permeability along the causative rupture zone or reactivating distant fault-fracture permeability by shaking from radiated waves. High-resolution geophysical investigations of active arc systems and the subduction thrust interface underlying their fore-arcs reveal repositories of overpressured hydrothermal fluids. In active magmatic arcs under compression such as NE Honshu or Cascadia, there is evidence for a heterogeneous distribution of overpressured hydrothermal fluids in the middle-to-lower crust trapped around the base of the upper crustal seismogenic zone. Investigations of the subduction thrust interface responsible for great (Mw = 8.0) ‘megathrust’ earthquake ruptures has revealed in some instances (Cascadia, SW Japan) the existence of a belt of non-volcanic tremor (NVT) with accompanying slow slip episodes defining the base of the megathrust interface at 40 ± 5 km and 350°C??-??550°C. Aqueous fluid at these depths is likely derived from dehydration reactions accompanying the basalt-eclogite transition in subducted oceanic crust. NVT sequences in the hanging-wall above the interface may be defining migration pathways into the overlying crust.The potential for eruptive episodes in magmatic arcs and redistribution of hydrothermal fluids is assessed in the light of the stress changes that followed the 2011 Mw9.0 Tohoku subduction thrust rupture which extended along strike for over 500 km and down-dip for over 150 km, with maximum slip of c 50 m.